The Making of 'Annabelle Blue': A Peircean Semiotic Analysis of the Creative Process - Porteous, Carol (Université d'Ottawa / University of Ottawa, 2014)
The paper discusses how the semiotic relationships involved in the process of creating a documentary, interconnect and affect the documentary's truth claims from the perspective of Peirce's semiotic theory. To do this, I created an autobiographical film called 'Annabelle Blue' and then analyzed the experience. The making of 'Annabelle Blue' involved a number of representations, each of which involved the interplay of iconic, indexical and symbolic elements and each of which had a substantial influence on how the process continued. It is my contention that documentary's truth claims must be evaluated in light of the assumption that documentary representation is a dynamic, creative process involving the jostling for position between semiotic aspects at every level.
Keywords: Documentary; Autobiography; Memory; Peirce; Semiotic; Film